Transformasi Hukum Perkawinan di Indonesia, Malaysia, dan Brunei Darussalam: Kajian Kritis atas Batas Usia Perkawinan dalam Perspektif Maqashid Syariah - Joni, Joni (Berasan: Journal of Islamic Civil Law, 2024)
This research aims to analyze the marriage age limit policy in Indonesia, Malaysia, and Brunei Darussalam as well as review its implications in the perspective of maqashid sharia. The research method used is a qualitative approach with a comparative study of the regulation of marriage laws in the three countries, supported by juridical and conceptual analysis within the framework of maslahah mursalah. The results of the research show that the age limit for marriage in Indonesia has been reformed with the enactment of Law Number 16 of 2019 which equalizes the minimum age of marriage for men and women to 19 years. Meanwhile, Malaysia still maintains a minimum age limit of 16 years for women and 18 years for men, despite the possibility of dispensation by sharia judges. In Brunei Darussalam, the regulation of the age limit for marriage is more varied and depends on ethnic and religious background, with most regulations allowing marriage at a lower age than international standards. The conclusion of this research affirms that the transformation of marriage law in the three countries shows that there is an effort to harmonize the principles of Islamic law and the protection of individual rights, especially in safeguarding the well-being of women and children. In the perspective of sharia maqashid, setting the marriage age limit aims to protect religion (ḥifẓ al-dīn), soul (ḥifẓ al-nafs), intellect (ḥifẓ al-‘aql), offspring (ḥifẓ al-nasl), and property (ḥifẓ al-māl). Law reform in Indonesia is more in line with the principle of protection for individuals, while Malaysia and Brunei still provide flexibility while maintaining traditional elements.